'Violence', Safety Crimes and Criminology - Tombs, Steve (The British journal of criminology, 2007)
While safety crimes far outweigh crimes of conventional' violence, British criminology continues to operate with rather narrow definitions of violence which exclude these. The aim of this paper is to examine the key ways in which occupational injury and death remain excluded by criminological definitions of violence. To do so, we review briefly three recent examples of approaches to, or discussions of, violence. Our discussions of each point to the general conclusion that criminological definitions of violence still fail to recognize offences against workers and the public arising out of work. The paper concludes by speculating on the preconditions for any such recognition, before noting frameworks for studying violence within which safety crimes, or corporate violence, are coherently accommodated